Engagement and Performance at Work: Relationship between Motivation, Concentration and Persistence in the Work Environment - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between Absorption, Dedication, and Vigor in the work environment, in order to understand how these engagement factors influence the employee experience within their organizations. The research is based on theoretical models on work commitment and organizational well-being, considering that a higher level of dedication and vigor can enhance absorption at work. It is hypothesized that employees with high levels of dedication and vigor have higher levels of absorption, which suggests that work commitment is an interdependent construct where each dimension contributes to the strengthening of the others. To evaluate this relationship, a quantitative design based on multiple linear regression was used. The estimated econometric model shows that the coefficients of the variables Dedication and Vigor are positive and highly significant (p<0.001p < 0.001), indicating that the increase in these factors is associated with an increase in absorption at work. In addition, the F-statistic test suggests that the model is significant at 99% confidence, allowing the results to be interpreted with a high level of reliability. The findings obtained indicate that work engagement is built from dynamic interactions between its dimensions, which has important implications for the design of organizational strategies aimed at improving the employee experience. It is recommended that future research incorporate moderating variables, such as workload or organizational resilience, in order to better understand the mechanisms that explain this relationship.